2019
DOI: 10.1590/1808-1657000582018
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of antibodies against Leptospira spp. in donkeys of São Paulo state

Abstract: Among the diseases that affect equines, bacterial diseases play an important role from a health and economic point of view, especially leptospirosis and brucellosis. The study aimed to provide information on the occurrence of anti-Leptospira spp. and anti-Brucella abortus antibodies in donkeys of São Paulo state. We found a frequency of 62.4% (53/85) antibodies against Leptospira spp. The donkeys were not seropositive for Brucella spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The most frequent serogroups in this study, Icterohaemorrhagiae and Ballum, have synanthropic rodents as their main reservoirs [ 3 , 34 , 35 ] and are of relevant importance in human leptospirosis [ 36 , 37 ]. Other serogroups found were Grippotyphosa, which is related to rodents or other wild animals [ 5 , 8 , 38 , 39 ]; Canicol, which has dogs as reservoirs [ 10 , 35 , 40 ]; and Semaranga, a saprophytic strain associated with cross−reactions involving many infectious serovars, often absent from the panel of serogroups used in the MAT [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent serogroups in this study, Icterohaemorrhagiae and Ballum, have synanthropic rodents as their main reservoirs [ 3 , 34 , 35 ] and are of relevant importance in human leptospirosis [ 36 , 37 ]. Other serogroups found were Grippotyphosa, which is related to rodents or other wild animals [ 5 , 8 , 38 , 39 ]; Canicol, which has dogs as reservoirs [ 10 , 35 , 40 ]; and Semaranga, a saprophytic strain associated with cross−reactions involving many infectious serovars, often absent from the panel of serogroups used in the MAT [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grippotyphosa and Hardjo; Pomona and Grippotyphosa, respectively (Samir et al, 2015;Ali & Safarmashaei, 2012;Benkirane et al, 2016;Esquivel et al, 2018). In São Paulo state in Brazil, a 2019 study found Icterohaemorrhagiae (41%) and Grippotyphosa (31%) in a group of 85 donkeys tested by the MAT (Lara et al, 2019).…”
Section: Discussionmentioning
confidence: 99%